EFEK INFUSA AKAR TEMPUYUNG (SONCHUS ARVENSIS) TERHADAP PENURUNAN KADAR ASAM URAT PADA TIKUS PUTIH (RATTUS NORVEGICUS) - Kurnia Retnowati; EM Sutrisna; Iin Novita Nurhidayati Mahmuda (Universitas Muhamadiyah Surakarta, 2014)
Tempuyung (Sonchus arvensis) consisted of fiavonoid were effect as obstruct xantine oksidase enzyme, antioxidant captur superoxsidase radical. The fiavonoid total in leave of tempuyung is 0,1044%, in its root have 0,5% fiavonoid and the more is apigenin-7-O-glikosida (3,4,5). This research aim to know effect of infusa root of tempuyung (Sonchus arvensis) to lower the uric acid level at blood serum and infusa root of Tempuyung (Sonchus arvensis) to lower the uric acid level at mouse blood serum compared to allopurinol.This research is laboratory experimental method. The object were 25 Wistar male mice 2-3 months old, 150-200 gr divided into 5 groups. Negative Control group given potassium oxonate by intraperitoneal, Positive Control group given potassium oxonate by intraperitoneal, added by allopurinol 18mg/kgBB, Infusa Concentrated Group 1 given potassium oxonate by intraperitoneal added by infusa root of tempuyung 1,25g/kgBB, Infusa Concentrated Group 2 given potassium oxonate by intraperitoneal added by infusa root of tempuyung 2,5g/kgBB, Infusa Concentrated Group 3 given potassium oxonate by intraperitoneal added by infuse root of tempuyung 5g/kgBB. Executed until one day, where measurement of uric acid of mouse blood serum done before and after treatment. Measurement of uric acid level is done by using spectrophotometer. Obtained to be data to be analysed with Kolgomorov-Smirnov test, One-Way ANOVA and continued with LSD (Least Significant Difference) test with 95% confidence interval (CI). Result of statistical test of research shoe that infusa root of Tempuyung (Sonchus arvensis) dose 1,25g/kgBB, 2,5g/ kgBB, 5g/kgBB have effect to lower the uric acid level at mouse blood serum. Infusa root of Tempuyung (Sonchus arvensis) concentrated 5g/kgBB proportional wih dose allopurinol 18mg/kgBB to lower the uric acid level at mouse blood serum.Keyword: Infusa, root of Tempuyung (Sonchus arvensis), uric acid